Global patterns and controlling factors of tree bark C : N : P stoichiometry in forest ecosystems consistent with biogeochemical niche hypothesis - Gong, Haiyang (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.